Fish condition in introduced tilapias of Ugandan crater lakes in relation to deforestation and fishing pressure - Efitre, Jackson; Chapman, Lauren J.; Murie, Debra J. (Environmental biology of fishes, 2009)
This study identifies environmental predictors of the condition of two introduced tilapia species (Oreochromis leucostictus and Tilapia zillii) that are known to have divergent trophic niches (planktivore and herbivore, respectively) in 17 crater lakes in western Uganda. We asked whether fish condition differs among lakes characterized by differences in fishing pressure and catchment deforestation; and we related relative condition factor to gradients of environmental variation across lakes. Lakes characterized by severe catchment deforestation tended to be lakes with high fishing pressure, so it was difficult to explore independent and interactive effects. However, mean relative condition factor was higher in populations with high fishing pressure compared to populations with low fishing pressure for both O. leucostictus and T. zillii. The condition of O. leucostictus populations was higher in lakes with severely deforested catchments; but mean relative condition factor of T. zillii did not differ between deforestation categories. Principal components analysis (PCA) was used to describe the major environmental gradients of variation among the lakes; and PCA factor scores were regressed against relative fish condition. The association between fish condition and environmental gradients was stronger for O. leucostictus than for T. zillii. For O. leucostictus, fish condition was related to PC1 (43% of the variance) and factors that loaded most heavily included Chl-a, water transparency, lake area and depth, suggesting higher condition in lakes characterized by higher primary productivity and smaller size. For T. zillii, PC3 (11%) was the only axis related to fish condition; and factors that loaded most heavily included lake area (positive), and conductivity and total nitrogen (negative). Some of the larger lakes are characterized by higher availability of macrophytes that may positively affect the food base for T. zillii.
Keywords: Human disturbance; Fishing pressure; Environmental predictors; Primary productivity; Oreochromis leucostictus; Tilapia zillii; Length-weight relationships